Room-level ventilation in schools and universities. (January 2022) - McNeill, V. Faye; Corsi, Richard; Huffman, J. Alex; King, Cathleen; Klein, Robert; Lamore, Michael; Maeng, Do Young; Miller, Shelly L.; Ng, Nga Lee; Olsiewski, Paula; Godri Pollitt, Krystal J.; Segalman, Rachel; et al.
Abstract: Ventilation is of primary concern for maintaining healthy indoor air quality and reducing the spread of airborne infectious disease, including COVID-19. In addition to building-level guidelines, increased attention is being placed on room-level ventilation. However, for many universities and schools, ventilation data on a room-by-room basis are not available for classrooms and other key spaces. We present an overview of approaches for measuring ventilation along with their advantages and disadvantages. We also present data from recent case studies for a variety of institutions across the United States, with various building ages, types, locations, and climates, highlighting their commonalities and differences, and examples of the use of this data to support decision making. Highlights: Room-level ventilation data supports decision making (filter use, HVAC scheduling). Controlled release studies provide ventilation data for naturally ventilated spaces. In situ monitoring of CO2 and PM can provide ventilation insights during occupancy. Natural ventilation can be high when cross flow is possible (open doors and windows). Natural ventilation in older buildings in colder climates is often inadequate.